ChemInform Abstract: Iridium‐Catalyzed Cycloaddition of Azides and 1‐Bromoalkynes at Room Temperature. Issue 6 (11th February 2014) - Rasolofonjatovo, Evelia; Theeramunkong, Sewan; Bouriaud, Alexandra; Kolodych, Sergii; Chaumontet, Manon; Taran, Frederic
Abstract The title mild reaction offers a direct route to new 1, 4, 5‐trisubstituted triazoles.